Perfluorocarbon-perfused 23 gauge three-dimensional vitrectomy for complicated diabetic tractional retinal detachment - Quiroz-Mercado H (Dove Medical Press, 2011)
Raul Velez-Montoya1, Jose Luis Guerrero-Naranjo2, Gerardo Garcia-Aguirre2, Virgilio Morales-Cantón2, Jans Fromow-Guerra2, Hugo Quiroz-Mercado31Department of Ophthalmology, University of Colorado Health and Science Center, Rocky Mountain Lions Eye Institute, University of Colorado School of Medicine, CO, USA; 2Retina Department, Asociación para Evitar la Ceguera en México IAP, México City, México; 3Department of Ophthalmology, Denver Health Medical Center, University of Colorado School of Medicine, Denver, CO, USABackground: Perfluorocarbon liquid (PCL)-perfused vitrectomy has been shown in previous studies to be feasible, safe, and to have advantages in managing complicated cases of tractional retinal detachment. The present study had the objectives of describing the anatomical results and measuring surgical time and PCL consumption when combining PCL-perfused techniques with modern vitrectomy equipment.Methods: A prospective, interventional consecutive case series was investigated. We enrolled patients with diabetic tractional retinal detachment, complicated by proliferative vitreoretinopathy and poor vision. A 23 gauge PCL-perfused vitrectomy was done with three-dimensional settings. During the procedure, we assessed the degree of surgical bleeding, visualization quality, and difficulty of membrane dissections. Visual acuity, intraocular pressure, and anatomical success were assessed at one and 3 months of follow-up.Results: Twelve patients were enrolled in this study. There were no statistical significant changes in intraocular pressure and visual acuity throughout the follow-up period. Surgery was performed in a hemorrhage-free environment in almost all cases, with good visualization and low technical difficulty. The mean complete surgical time was 94.92 ± 25.03 minutes. The mean effective vitrectomy time was 22.50 ± 19.04 minutes and the mean PCL consumption was 25.08 ± 9.76 mL, with a speed of 1.11 mL/minute. Anatomical success was 67% at 3 months.Conclusion: Although the technique proved to have some advantages in managing complicated cases of diabetic tractional retinal detachment, there was a high consumption of PCL. A redesign of the entire system is needed in order to decrease the amount of PCL needed for the technique.Keywords: retinal detachment, diabetic, surgery, vitrectomy, vitreoretinopathy, perfluorocarbon